Organic residues from agricultural and forest companies in Brazil as useful substrates for cultivation of the edible mushroom Pleurotus ostreatus - Viriato, V. [UNESP]; Mäkelä, M. R.; Kowalczyk, J. E.; Ballarin, C. S. [UNESP]; Loiola, P. P. [UNESP]; Andrade, M. C.N. [UNESP] (Oxford University Press (OUP), 2022)
We investigated whether highly available organic residues in Brazil can be used as substrates for the production of the oyster mushroom Pleurotus ostreatus, instead of the conventional cultivation using the eucalyptus sawdust substrate. We assessed the mushroom yield on 13 substrates, of which 12 were formulated with different concentrations of organic residues and one with pure eucalyptus sawdust, and verified whether the raw material used in the substrate formula and the concentration of such alternative residues influenced their biological efficiencies. Substrates containing eucalyptus bark resulted in higher mushroom yield than those containing eucalyptus sawdust, which generally resulted in similar mushroom yield to the remaining formulas. Moreover, the raw material and the concentration of each residue affected the biological efficiency of the substrates. We show that the conventional substrate for P. ostreatus can be replaced by substrates easily accessible to producers without loss in productivity. Furthermore, that the concentration of these mixtures affects the mushroom productivity and should be considered when formulating the growth medium.